Targeting eotaxin‐1 and CCR3 receptor alleviates enteric neuropathy and colonic dysfunction in TNBS‐induced colitis in guinea pigs. Issue 11 (3rd July 2018) - Filippone, R. T.; Robinson, A. M.; Jovanovska, V.; Stavely, R.; Apostolopoulos, V.; Bornstein, J. C.; Nurgali, K.
Abstract: Background: The accumulation of eosinophils is mediated by the chemokine receptor‐3 (CCR3)‐eotaxin axis. Increased expression of eotaxin and its receptor is associated with inflammatory bowel disease (IBD). Activation of eosinophils causes the release of cationic proteins that are neurotoxic such as eosinophil‐derived neurotoxin (EDN). Damage to enteric neurons alters neurally controlled functions of the gut correlated with intestinal inflammation. We hypothesized that inhibition of the CCR3‐eotaxin axis will prevent inflammation‐induced functional changes to the gastrointestinal tract. Methods: Hartley guinea pigs were administered with trinitrobenzene sulfonate (TNBS; 30 mg/kg in 30% ethanol) intrarectally to induce colitis. A CCR3 receptor antagonist (SB 328437 [SB3]) was injected intraperitoneally 1 hour postinduction of colitis. Animals were euthanized 7 days post‐treatment and colon tissues were collected for ex vivo studies. The EDN‐positive eosinophils in the colon, indicating eosinophil activation, were quantified by immunohistochemistry. Effects of SB3 treatment on gross morphological damage, enteric neuropathy, and colonic dysmotility were determined by histology, immunohistochemistry, and organ bath experiments. Key Results: The number of EDN‐positive eosinophils was significantly increased in the lamina propria in close proximity to myenteric ganglia in inflamed colon. The TNBS‐induced inflammation caused significant damage to colonic architecture and inhibition of colonic motility. Treatment with SB3 antagonist attenuated inflammation‐associated morphological damage in the colon, reduced infiltration of EDN‐positive eosinophils and restored colonic motility to levels comparable to control and sham‐treated guinea pigs. Conclusion & Inferences: This is the first study demonstrating that inhibition of CCR3‐eotaxin axis alleviates enteric neuropathy and restores functional changes in the gut associated with TNBS‐induced colitis. Abstract : Eosinophil accumulation is mediated by the chemokine receptor‐3 (CCR3)‐eotaxin axis. Treatment with a CCR3 receptor antagonist attenuated inflammation‐associated morphological damage in the colon, reduced infiltration of EDN‐positive eosinophils, and restored colonic motility to levels comparable to control and sham‐treated guinea pigs. Inhibition of CCR3‐eotaxin axis alleviates enteric neuropathy and restores functional changes in the gut associated with TNBS‐induced colitis.